TEACHING METHODOLOGY: THE LESSON ON THE TOPIC “AGREEMENT ON THE UNCOMPENSATED USE OF PROPERTY (LOAN)” - V. N. Sinelnikova (Финансы: теория и практика)
The author shares her experience of training the students of the law faculty on the theme “Agreement on uncompensated use (loan)”. Many lecturers do not pay due attention to this topic, considering it as archaic in the market relations conditions. Indeed, the loan agreements are often categorized as fiduciary transactions. Therefore, the lecturer must arrange activities in a way to show not only the relevance of loans for family or friendly relations but also to bring compelling arguments of its effectiveness while carrying out business or other income-generating activities. At the same time, it should be noted that the students already possess the basics of legal knowledge, but still have poorly competencies in analysis of special norms and their practical application. For this purpose, the article provides a brief historical investigation into the Agreement on the uncompensated use of property, reviews its concept and elements, shows its relationship with adjacent types of transactions, and identifies some problems linked to the use of the loan agreement under market conditions. In closing, the author formulates the questions to help students improve their skills. The article might be of interest to teachers, post-graduates and students studying the second part of the civil law.